2012
DOI: 10.1515/hf-2012-0034
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of xylans from Eucalyptus species. Part 1. The influence of structural features of eucalyptus xylans on their retention in kraft pulp

Abstract: 4-O -methylglucuronoxylans were isolated from the wood and pulp of different Eucalyptus species ( E. dunni, E. grandis, E. nitens, E. urograndis and E. urophylla) and characterized by 1 H NMR spectroscopy and size-exclusion chromatography (SEC). The content of 4-O -methylglucuronic acid (MeGlcA) varied between the eucalyptus species from 1.90 to 2.80 expressed as MeGlcA/10 xyloses, whereas in the pulp, the total uronic acid content was approximately 1.02, from which the half was hexenuronic acid (HexA). From … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…[23] Studies with different Eucalyptus species showed that the lower degradation of xylans during kraft pulping could be associated with a higher molar mass or more branched chains of the polysaccharide with MeGlcA. [8,9] For our samples, MeGlcA per 10 xylose units (determined by acid methanolysis) were in the range of 1.03-1.37 and 0.79-0.87 for samples of groups I and II, respectively, which supports the previous results.…”
Section: Chemistry and Pulping Of E Globulus Genotypessupporting
confidence: 86%
See 4 more Smart Citations
“…[23] Studies with different Eucalyptus species showed that the lower degradation of xylans during kraft pulping could be associated with a higher molar mass or more branched chains of the polysaccharide with MeGlcA. [8,9] For our samples, MeGlcA per 10 xylose units (determined by acid methanolysis) were in the range of 1.03-1.37 and 0.79-0.87 for samples of groups I and II, respectively, which supports the previous results.…”
Section: Chemistry and Pulping Of E Globulus Genotypessupporting
confidence: 86%
“…[7,17,21,22] The The degree of substitution (DS) of the xylose residues with MeGlcA and HexA ( Table 2) was calculated by the integration of the corresponding signals in the 1 H-NMR spectra, following the procedures described elsewhere. [7,9,17,21,22] Xylans isolated from wood holocellulose of samples from group I presented high DS with MeGlcA (1.4 to 1.9 MeGlcA/10 xylose units) in comparison with xylans from group II (0.9 to 1.3 MeGlcA/10 xylose units). As previously reported, these values are usually higher than those determined by acid methanolysis.…”
Section: H-nmr Of Isolated Xylansmentioning
confidence: 98%
See 3 more Smart Citations